Adjuvants as Part of Anaesthetic Care in Prevention of Postoperative Nausea and Vomiting - D. S. Baskakov; V. E. Khoronenko (Общая реаниматология)
Study Objective: to assess the efficacy and safety of different combinations of antiemetic drugs and adjuvants as part of anesthetic care in prevention of postoperative nausea and vomiting in oncological patients. Materials and methods: 165 patients who undergone surgical treatment for female oncological diseases on the II—III stages with common anaesthesia were included. Depending on the scheme of postoperative nausea and vomiting prevention participants were divided into 4 groups. Patients from group С (comparative, n=43) received treatment with ondansetron (8 mg) and dexamethasone (8 mg) in the induction stage. Patients from group E (n=40) additionnaly received continuous infusion of esmolol 0,59±0,94 mg/kg/h. Patients from group D (n=41) on the traumatic stage of operation received bolus of intravenous droperidol 0,038±0,055 mg/kg. Patients from group K (n=41) on the traumatic stage of operation received bolus of intravenous of clonidine 0,0013±0,0004 mg/kg. Postoperative nausea and vomiting episodes were monitored during 24 hours after the surgery. Results: in group С postoperative nausea and vomiting developed in 15 patients from 43 (34,9%). In group E this complication was detected in 8 from 40 patients (20%). In group D – in 8 from 41 patients (19,5%). Groups E and D did not have statistically significant differences from group С in terms of the frequency of postoperative nausea and vomiting. In group С this complication was detected in 6 from 41 patients with the rate of 14,6% which is significantly lower than in group С (p=0.03). The intensity of the nausea and vomiting was lower in groups E,D, and K as compared with group С. Conclusion: the inclusion of clonidine in scheme of postoperative nausea and vomiting prevention lead to statistically significant decrease of the frequency of this complication. Administration of esmolol and droperidol leads to decrease of postoperative nausea and vomiting intensity. Key words: oncosurgey, postoperative nausea and vomit_ ing, antiemetics, esmolol, droperidone, clonidine.